Faktor Faktor Yang Mempengaruhi Keputusan Masyarakat Terhadap Penerapan Waste Management Di Lingkungan Rumah Tangga Kota Surakarta - Anwar, Muhammad Fathul; Retnaningsih, Nugraheni; Dewati, Rosita; Harinta, Yos Wahyu; Nursamsi (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2025)
The low level of public awareness regarding behavior that allows food waste to occur, as well as weak household waste management institutions in the Surakarta City environment, are important obstacles for the Surakarta City Government in implementing its waste management system. This research was conducted to find out what factors influence the community's decision to implement Waste Management in the household environment in Surakarta City, so that it can become a benchmark for waste management in each household environment. The method used was descriptive and analytical, with 130 respondents from five sub-districts in Surakarta City, and analyzed using logistic regression analysis.. Through logistic regression analysis, a regression model was produced with an Overall Percentage value of 84.00 percent, which indicates that the resulting model is good. Through this analysis, the equation model was obtained Z = 1.505 – 0.203 KEL + 3.848 AGE – 1.144 LAM – 4.101 PROD. Variables that influence people's decisions in implementing food waste-based waste management in household environments in Surakarta City include the variables age, length of stay and daily waste production with a significance level (α) of 10 percent.